Novel triazole-sulfonamide bearing pyrimidine moieties with carbonic anhydrase inhibitory action: Design, synthesis, computational and enzyme inhibition studies. (15th September 2021) - Manzoor, Shoaib; Petreni, Andrea; Raza, Md Kausar; Supuran, Claudiu T.; Hoda, Nasimul
Graphical abstract: Highlights: A series of novel triazole-sulfonamide based pyrimidine compounds as carbonic anhydrase (CA) inhibitors are reported. Compounds were evaluated against four CA isoforms like h CA I, II, IX, XII. SH-20, SH-26 and SH-28 compounds exhibited significant inhibitory activity and selectivity profile against the h CA XII. SH-23 displayed significant selectivity towards tumor-associated h CA IX and XII. Abstract: A series of new triazole-sulfonamide bearing pyrimidine derivatives were designed and synthesized via click chemistry. All new compounds (SH-1 to SH-28 ) were validated by 1 HNMR, 13 CNMR, HRMS, and SH-3 was further structurally validated by X-Ray single diffraction study. These compounds (SH-1 to SH-28 ) were tested as inhibitors of human carbonic anhydrase ( h CA) isoforms, such as h CA I, II, IX and XII, using a stopped flow CO2 hydrase assay. Most of the compounds exhibited significant inhibitory activity against h CA II and weak inhibitory activity against h CA I. The target compounds also displayed moderate to excellent inhibitory activity against tumor-related h CAs IX and XII. Some compounds, e.g., SH-20 (Ki  = 9.4 nM), SH-26 (Ki  = 1.8 nM) and SH-28 (Ki  = 0.82 nM) exhibited excellent inhibitory activity and selectivity profile against h CAs XII over IX. SH-23 displayed promising inhibitory activity and selectivity profile against both tumor-related h CAs IX (Ki = 2.9 nM) as well as XII (Ki = 0.82 nM) over h CA I and II. To understand the molecular interactions, molecular docking study of compounds SH-20, SH-23, SH-26 and SH-28 with h CA XII and SH-23 also with h CA IX were performed. The computational study evidenced favorable interaction between the inhibitors and active residues of both proteins. Some of these derivatives are promising leads for the development of selective, anticancer agents based on CA inhibitors.